2018
DOI: 10.1002/prca.201700119
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy to Investigate Tissue‐Secreted Tumor Microenvironmental Proteins in Serum toward Development of Breast Cancer Early Diagnosis Biomarker Signature

Abstract: Purpose: The study aims to discover and identify early grade diagnosis markers in tumor microenvironment and investigates their expression in serum. Experimental design: 2D fluorescence difference gel electrophoresis (2D-DIGE), a gel-based proteomics platform is used for tissue profiling and identifies deregulated proteins by matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry. Western blot validation for statistically significant six different proteins is performed in an independent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the other hand, differently expressed proteins in the serum of breast cancer patients vs. controls have been described (39). The deregulated proteins found in the pools of cancer vs. control serum samples-PEDF, IGKC, CD44, and CST3-have been previously reported (39)(40)(41).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, differently expressed proteins in the serum of breast cancer patients vs. controls have been described (39). The deregulated proteins found in the pools of cancer vs. control serum samples-PEDF, IGKC, CD44, and CST3-have been previously reported (39)(40)(41).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, differently expressed proteins in the serum of breast cancer patients vs. controls have been described (39). The deregulated proteins found in the pools of cancer vs. control serum samples-PEDF, IGKC, CD44, and CST3-have been previously reported (39)(40)(41). High levels of CD44 in serum are an independent prognosis indicator in primary breast cancer, since it correlates with overall survival and disease-free survival (42).…”
Section: Discussionmentioning
confidence: 99%
“…One of these is HS90B, which was also present in EXOs isolated from five GBM cell lines [110], and shows a potential functional network with other important molecules with co-chaperone activities (see Figure 3 and Table S4). Indeed, HS90B has a role in cancer progression, together with proteins including GRP75 and VIME (reported in our Table 1), and as a potential biomarker, useful for diagnostic and therapeutic applications in malignant melanoma cancer [111] or early grade breast cancer [112]. Furthermore, it has been related to tumors' chemo-and radio-resistance, also showing angiogenic properties [101].…”
Section: Discussionmentioning
confidence: 86%
“…Gelsolin, Protein Daple, Heat shock protein HSP 90-beta, Alpha-1-antitrypsin, and Cathepsin D constitute serum biomarker signature for diagnosing early grade breast cancer. The panel of proteins also provides crucial information for a better understanding of molecular mechanisms underlying the inceptive stage of breast cancer [104]. Recently, Gomig et al [105] showed a high similarity in the proteomic profile between contralateral and adjacent nontumor breast tissues.…”
Section: Discussionmentioning
confidence: 99%